2021
DOI: 10.9734/ajsspn/2021/v7i430117
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Organic and Inorganic Fertilizers Applications Levels on Greenhouse Tomato (Solanum lycopersicum) Yield and Soil Quality in Khost Province

Abstract: The study was carried out to determine the effect of organic and inorganic fertilizers on tomato yield and soil quality.  The study was performed in a randomized complete block design consisting of 7 treatments with 3 replications in the research farm, Shaikh Zayed University, Khost, Afghanistan. The fertilizers treatments were T1, organic fertilizer (5 t/ha); T2, organic fertilizer (10 t/ha); T3, urea (150 Kg/ha); T4, urea (200 Kg/ha); T5, mixed fertilizers (organic fertilizer 3 t/ha + urea (100 Kg/ha); T6, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…The more availability of nutrients under higher levels might have encouraged the photosynthesis, accumulation of food material and higher plant growth resulting in more plant height. These results are in accordance with the findings of Ali et al [10], Singh et al [11] and Hashimi et al [12].…”
Section: Plant Heightsupporting
confidence: 93%
“…The more availability of nutrients under higher levels might have encouraged the photosynthesis, accumulation of food material and higher plant growth resulting in more plant height. These results are in accordance with the findings of Ali et al [10], Singh et al [11] and Hashimi et al [12].…”
Section: Plant Heightsupporting
confidence: 93%
“…The global increase in population, coupled with concerns about the indiscriminate use of agrochemicals, has highlighted the significance of organic farming [13]. Organic fertilizers, such as farmyard manure (FYM), goat manure, poultry manure, and biofertilizers, have gained attention as substitutes for chemical or inorganic fertilizers in cultivating baby spinach [14]. Reports suggest that organic fertilizers offer several benefits, including improved soil aggregation and physical properties like water retention and aeration.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, when more leaf litter was added together with a manure amendment, the amounts of N, Zn, Fe, Cu, and Cd in spinach decreased. (Hashimi et al, 2019) indicated that cow manure application without applied N showed adverse impact on spinach yields. (Kaho et al, 2020) results showed that the height of the plants, number of leaves, the fresh weight, and the dry weight of spinach (Amaranthus spp.)…”
Section: Introductionmentioning
confidence: 99%